Drivers of spatial change in urban housing submarkets. Issue 4 (30th May 2019) - Costello, Greg; Leishman, Chris; Rowley, Steven; Watkins, Craig
Abstract : Spatial urban housing submarkets are now widely used constructs. Recent housing market modelling strategies have emphasised the need for flexibility in modelling approaches in order to best accommodate submarkets which account for spatial variations in hedonic prices. But this raises important unanswered questions concerning the stability of submarket structures over time, and the role of housing market dynamics in breaking down or shifting submarket boundaries. The influence of new supply, in particular, may have a stabilising or destabilising effect on differences in hedonic prices, depending on the wider housing market context. In this paper we examine the temporal influence of new supply, intra‐urban migration and socio‐economic change as a means of understanding the impact of key drivers of submarket boundary change. Using the Greater Perth region of Western Australia as a case study, we estimate income elasticities of demand for housing services that vary spatially within the urban area. We find evidence that higher income elasticities, new development, socio‐economic change and intra‐urban migration are associated with changes in the spatial structure of housing prices within the metropolitan housing market. Abstract : In this paper we examine the temporal influence of new supply, intra‐urban migration and socio‐economic change as a means of understanding the impact of key drivers of submarket boundary change. Based on a study of the Greater Perth region of Western Australia, we find evidence that higher income elasticities, new development, socio‐economic change and intra‐urban migration are associated with changes in the spatial structure of housing prices within the metropolitan housing market.